Legionella pneumophila balances ubiquitin transglutamination. (28th January 2020) - Yan, Fujie; Zhu, Yongqun; Zhou, Yan
Abstract : The effector MavC of the bacterial pathogen Legionella pneumophila catalyzes a noncanonical ubiquitination of the host ubiquitin‐conjugating E2 enzyme UBE2N by crosslinking a glutamine residue of ubiquitin to UBE2N lysine residues via its transglutaminase activity. A new study by Gan et al (2020) reveals that L. pneumophila reverses this noncanonical ubiquitination via its ubiquitin deamidase effector MvcA to allow precise temporal regulation of host signaling during infection. Abstract : A new study reveals that L. pneumophila employs a non‐canonical ubiquitination/de‐ubiqutination cascade to allow precise temporal regulation of host immune response during infection.